Characterization of simple magnetorheological fluids with potential application in engineering - Mesquida, César Darío (2014)
In this work, the authors wonder if it is possible to easily create affordable and simple-made magnetorheological fluids with interesting properties in order to design speed control devices. The focus is on simplicity and magnetorheological characterization. In that way, this paper describes the experiments done with magnetorheological fluids (MRF) which were designed, developed and tested. Studied fluids were easily prepared. Their chosen components are widely used in local industry. The magnetic fields used were generated with permanent magnets from commercial availability. Two types of fluids were created. One of them was composed of iron oxide particles widely used in non destructive tests (NDT) in the petroleum industry. The other component was printer?s toner. These fluids were manufactured and experimented with different concentrations of magnetic material and also with different additives in order to avoid sedimentation and agglomeration. In all cases, circumferential flow was studied in cylindrical containers subjected to stationary, unidirectional, transverse magnetic fields. Significant increments of viscosity against imposed magnetic fields are highlighted. Unfortunately, it was not possible to prevent particle sedimentation without making more complex, expensive and difficult to create the fluids. However, a good redispersion is observed when these fluids are stirred. From these results, the design of magnetorheological devices employing MRF with the characteristics studied for control applications is planned. This paper aims to describe the behavior of magnetorheological fluids created in simple steps and from elements widely used in industry in order to obtain an application in engineering.